Efficacy and safety of thalidomide for the treatment of severe recurrent epistaxis in hereditary haemorrhagic telangiectasia: results of a non-randomised, single-centre, phase 2 study. Issue 11 (November 2015) - Invernizzi, Rosangela; Quaglia, Federica; Klersy, Catherine; Pagella, Fabio; Ornati, Federica; Chu, Francesco; Matti, Elina; Spinozzi, Giuseppe; Plumitallo, Sara; Grignani, Pierangela; Olivieri, Carla; Bastia, Raffaella; et al.
Summary: Background: Hereditary haemorrhagic telangiectasia is a genetic disease that leads to multiregional angiodysplasia. Severe recurrent epistaxis is the most common presentation, frequently leading to severe anaemia. Several therapeutic approaches have been investigated, but they are mostly palliative and have had variable results. We aimed to assess the efficacy of thalidomide for the reduction of epistaxis in patients with hereditary haemorrhagic telangiectasia that is refractory to standard therapy. Methods: We recruited patients aged 17 years or older with hereditary haemorrhagic telangiectasia who had severe recurrent epistaxis refractory to minimally invasive surgical procedures into an open-label, phase 2, non-randomised, single-centre study at IRCCS Policlinico San Matteo Foundation (Pavia, Italy). We gave patients thalidomide at a starting dose of 50 mg/day orally. If they had no response, we increased the thalidomide dose by 50 mg/day increments every 4 weeks, until a response was seen, up to a maximum dose of 200 mg/day. After patients had achieved a response, they continued treatment for 8–16 additional weeks. The primary endpoint was the efficacy of thalidomide measured as the percentage of patients who had reductions of at least one grade in the frequency, intensity, or duration of epistaxis. We followed up patients each month to assess epistaxis severity score and transfusion need, and any adverse events were reported. We included all patients who received any study drug and who participated in at least one post-baseline assessment in the primary efficacy population. The safety population consisted of all patients who received any dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT01485224 . Findings: Between Dec 1, 2011, and May 12, 2014, we enrolled 31 patients. Median follow-up was 15·9 months (IQR 10·1–22·3). Three (10%, 95% CI 2–26) patients had a complete response, with bleeding stopped, 28 (90%, 95% CI 74–98) patients had partial responses. Overall, all 31 (100%, 89–100) patients responded to therapy with a significant decrease in all epistaxis parameters (p<0·0001 for frequency, intensity, and duration). A response was achieved by 25 (81%) patients at 50 mg/day of thalidomide, five (16%) patients at 100 mg/day, and one (3%) patient at 150 mg/day. Patients had only non-serious, grade 1 adverse effects, the most common of which were constipation (21 patients), drowsiness (six patients), and peripheral oedema (eight patients). One patient died a month after the end of treatment, but this was not deemed to be related to treatment. Interpretation: Low-dose thalidomide seems to be safe and effective for the reduction of epistaxis in patients with hereditary haemorrhagic telangiectasia. Our findings should be validated by further studies with larger patient populations, longer follow-up, and that also assess the benefit for quality of life. Funding: Telethon Foundation.